PREMARITAL SEXUAL BEHAVIOR AMONG UNIVERSITY STUDENTS IN SURABAYA: PATTERNS, MOTIVATIONS, AND SOCIAL INFLUENCES - Rifah, Erwin Nur; Sri Affirda; Dwi Martiana Wati (IAKMI South Tangerang Branch, 2025)
Background: Premarital sexual behavior among young people remains a critical reproductive health concern, particularly in urban university settings where permissive lifestyles and strong peer influence prevail.Objective: This study aimed to explore the patterns, motivations, and social influences underlying premarital sexual behavior among university students in Surabaya. Methods: A qualitative case study was conducted between January and June 2023. Data were collected through in-depth interviews with 11 informants aged 19–24 years, consisting of five students who engaged in premarital sexual behavior, five peer informants, and one key informant. The data were analyzed using thematic analysis with open coding, and credibility was ensured through source triangulation. Results: Sexual activities ranging from petting to sexual intercourse, occurring within romantic relationships and Friends with Benefits (FWB) arrangements, were widely perceived as normative. Motivations varied by gender, with male participants citing biological drives and female participants emphasizing emotional intimacy. Peer groups played a dominant role in normalizing these behaviors, often outweighing parental and religious influences, which were constrained by cultural taboos. Conclusion: Premarital sexual behavior among university students has shifted toward more casual patterns, primarily driven by peer group norms. Universities should establish student-friendly counseling services and strengthen peer counselor programs to promote healthy relationships, consent, and harm reduction, rather than focusing solely on abstinence-based approaches.